Ignition Transition of Coaxial Kerosene/Gaseous Oxygen Jet. Issue 11 (1st December 2016) - Kim, Dohun; Son, Min; Koo, Jaye
ABSTRACT: The pressure and temperature during liquid rocket engine ignition drastically increase because of energy generation from the severe combustion reaction of pure oxidizer and fuel. Studies on the ignition of oxygen/kerosene combustion are scarce. This research observes ignition transition of a gaseous oxygen/kerosene spray by directly visualizing the combustion flow field using a windowed combustor and high-speed shadowgraph imaging technique. The hydrodynamic characteristics of a propellant feed system are investigated before the ignition experiments by analyzing the time responses of propellant injection pressures and a high-speed movie of developing spray during injection. The experiments are performed with a 22.5 ms fuel pre-injection sequence. The high-speed shadowgraph imaging and dynamic pressure measurement results are analyzed. The effects of ignition timing on the ignition transition are focused on. The early ignition timing results in the smoothest ignition and longest ignition delay time from the propellant injection related to an ignitable transient spray condition. The combustion pressure rapidly increases with ignition timing delay. A peak pressure caused by propellant mixture accumulation is also observed. The ignition delay is less than 5 ms, and slightly decreases as the ignition timing is further delayed.